Maintaining mission critical systems in a 24/7 environment - Curtis, Peter M. (Wiley-IEEE Press, 2021)
"Continuous, clean, and uninterrupted power and cooling is the lifeblood of any data center, especially one that operates 24 hours a day, 7 days a week. Critical enterprise power is the power without which an organization would quickly be unable to achieve its business objectives. Today, more than ever, enterprises of all types and sizes are demanding 24-hour system availability. This means enterprises must have 24-hour power and cooling day after day, year after year. One such example is the banking and financial services industry. Business practices mandate continuous uptime for all computer and network equipment to facilitate round-the-clock trading and banking processes anywhere, and everywhere, from any device in the world. Banking and financial service firms are completely intolerant of unscheduled downtime, given the guaranteed loss of business that invariably results. However, providing the best equipment is not enough to ensure 24-hour operation throughout the year. The goal is to achieve reliable 24-hour power, cooling, and processing at all times, regardless of the technological sophistication of the equipment or the demands placed upon that equipment by the end-user, be it business or municipality"--
Includes bibliographical references and index
Description based on print version record and CIP data provided by publisher; resource not viewed